UNA REMINISCENCIA PLATÓNICA EN FILÓN DE ALEJANDRÍA (R. 2.377-9 EN SPEC. 1.28-30) - Carolina Delgado (Exemplaria Classica, 2016)
This article explores two texts, R. 2.377- 9 and Spec. 1.28-30; there the thinkers undertake an analysis of the myths. Con- fronting the sections, we have noted (i) a strong textual relationship between these two texts, and (ii) a Philonian remarkable appropriation of the Platonic criticism to myth.